Complement and Chlamydia psittaci: Early Complement-Dependent Events Are Important for DC Migration and Protection During Mouse Lung Infection - Kohn, Martin; Lanfermann, Christian; Laudeley, Robert; Glage, Silke; Rheinheimer, Claudia; Klos, Andreas (Frontiers in Immunology, 2021)
The zoonotic intracellular bacterium Chlamydia psittaci causes life-threatening pneumonia in humans. During mouse lung infection, complement factor C3 and the anaphylatoxin C3a augment protection against C. psittaci by a so far unknown mechanism. To clarify how complement contributes to the early, innate and the late, specific immune response and resulting protection, this study addresses the amount of C3, the timing when its presence is required as well as the anaphylatoxin receptor(s) mediating its effects and the complement-dependent migration of dendritic cells. Challenge experiments with C. psittaci on various complement KO mice were combined with transient decomplementation by pharmacological treatment, as well as the analysis of in vivo dendritic cells migration. Our findings reveal that a plasma concentration of C3 close to wildtype levels was required to achieve full protection. The diminished levels of C3 of heterozygote C3+/- mice permitted already relative effective protection and improved survival as compared to C3-/- mice, but overall recovery of these animals was delayed. Complement was in particular required during the first days of infection. However, additionally, it seems to support protection at later stages. Migration of CD103+ dendritic cells from the infected lung to the draining lymph node - as prerequisite of antigen presentation - depended on C3 and C3aR and/or C5aR. Our results provide unique mechanistic insight in various aspects of complement-dependent immune responses under almost identical, rather physiological experimental conditions. Our study contributes to an improved understanding of the role of complement, and C3a in particular, in infections by intracellular bacteria.